Pelatihan Penulisan Proposal Penelitian Melalui Metode Mind-Mapping - Fatimah Hidayahni Amin; Nurharsya Khaer Hanafie; Amirullah Amirullah; Seny Luhriyani; Riny Jefri (Universitas Negeri Makassar, 2023)
This study aims to describe the training of research proposal writing using mind-mapping method. The training method used was counseling. This outreach activity is divided into three, namely mapping the introduction or preparation of Chapter 1, mapping the theoretical reviews or preparation of Chapter 2, and mapping the research methodology or preparation of Chapter 3. The PKM participants are students of Bahasa Inggris Program Sarjana Terapan Study Program, Universitas Negeri Makassar who were selected randomly purposive. The results of the training showed that PKM participants were able to produce background writing that was easy to understand and practical in Chapter 1, produce structured literature descriptions in Chapter 2, and produce procedural mapping of research method writing in Chapter 3. Mind mapping activities help PKM participants to be able to formulate operational definitions of research variables, identify theories or concepts in literature studies, find trusted and credible sources of information, and determine research methods.